INVESTIGATION OF POSTGRADUATE STUDIES ON EDUCATION PROGRAM: A CONTENT ANALYSIS - Kazu, İbrahim Yaşar; Çam, Hüseyin (My University, 2021)
The aim of this study is to examine the master’s and doctoral theses published in the fields ofeducation programs according to the determined criteria. The research being in a scanningmodel, was carried out based on a content analysis. In this study, postgraduate theses publishedat the CHE National Thesis Center which was open to access between 2018 and 2020 wereexamined. Additionally, 91 postgraduate theses reached by purposeful sampling method wereanalyzed with the assistance of thesis examination form created by the researcher. For this mainpurpose, the thesis was evaluated in terms of the university, institute, department, year, method,data collection tools, sample type and program dimension. In addition to these data, analyzeswere made on which education level and dimension of the education program the postgraduatestudies were directed. Re-coding reliability was calculated in order to ensure the reliability of thestudy. The data obtained were interpreted based on percentage and frequency. It was concludedthat the highest number of studies were carried out at Gazi University, in educational sciencesinstitute, in the field of education programs and teaching. As a result, in terms of the methodsused, it was observed that the qualitative research method was mostly used and the studies inthe program evaluation type were more intense. The research is important in terms of guidingresearchers by revealing the trends of postgraduate studies.
Keywords: Eğitim; Eğitim Araştırmaları